Mod en ny fransk litteratur - Problemer og tendenser - Baggesgaard, Mads Anders (Passage - Tidsskrift for litteratur og kritik, 2012)
Mads Anders Baggesgaard: “Towards a New French Literature. Problems and Tendencies” The landscape of new French literature is not easily described. The very task entails a number of historical problems, ranging from the very idea of newness itself to the notion of a national, French literature in an increasingly globalized world. This article tackles the problem by delineating three different tendencies in contemporary French literature: A strand of mediarealism, exemplified by Fréderic Beigbeder, a realistic trend, exemplified by François Bon, and an autofictional trend exemplified by Serge Doubrovsky. However, these are not simply taken as examples; the article also aims to show that these different tendencies can in fact be read as different reflections on the historiographical problems facing French literature today.